Media Treatment of Monetary Policy Surprises and Their Impact on Firms' and Consumers' Expectations - Julien Pinter; Evzen Kocenda (Charles University in Prague, Institute of Economic Studies (IES), 2021)
We empirically investigate whether monetary policy announcements affect firms' and consumers' expectations by taking into account media treatments of monetary policy announcements. To identify exogenous changes in monetary policy stances, we use the standard financial monetary policy surprise measures in the euro area. We then analyze how a general newspaper and a financial newspaper (Le Monde and The Financial Times) report on announcements. We find that 87 % of monetary policy surprises are either not associated with the general newspaper reporting a change in the monetary policy stance to their readers or have a sign that is inconsistent with the media report of the announcement. When we use the raw monetary policy surprises variable as an independent variable in the link between monetary policy announcements and firms'/consumers' expectations, we mostly do not find, in line with several previous studies, any statistically significant association. When we take only monetary policy surprises that are consistent with the general newspaper report, in almost all cases we find that monetary policy surprises on the immediate monetary policy stance do affect expectations. Surprises related to future policy inclination and information shocks usually do not appear to matter. The results appear to be in line with rational inattention theories and highlight the need for caution in the use of monetary policy surprise measures for macroeconomic investigations.
Keywords: D84; E02; E52; E31; 330; firm expectations; consumer expectations; monetary policy surprises; European Central Bank; information effect